1994
DOI: 10.1042/bj2970031
|View full text |Cite
|
Sign up to set email alerts
|

Desulphation of dextran sulphate during kidney ultrafiltration

Abstract: The renal clearance of [3H]dextran sulphate by the isolated perfused rat kidney was associated with desulphation of the molecule, as demonstrated by ion-exchange and affinity chromatography of material resident in both glomeruli and urine samples. This process also occurred in vivo. The molecular size distribution of glomerular dextran sulphate in the perfused kidney was indistinguishable from that in the perfusate, and although urinary material was smaller it remained macromolecular. Sulphatase activity was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 16 publications
2
22
1
Order By: Relevance
“…Opposing that coherent body of theory and experiment are other data suggesting that some of the apparent charge selectivity may be artifactual, due to cellular processing of charged solutes (7). More recent papers demonstrate both enhanced transport of anionic tracers compared with neutral ones and in vivo studies in which reducing the charge of the basement membrane gel had negligible effect on permselectivity to albumin (3,6,20,22,35).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Opposing that coherent body of theory and experiment are other data suggesting that some of the apparent charge selectivity may be artifactual, due to cellular processing of charged solutes (7). More recent papers demonstrate both enhanced transport of anionic tracers compared with neutral ones and in vivo studies in which reducing the charge of the basement membrane gel had negligible effect on permselectivity to albumin (3,6,20,22,35).…”
Section: Discussionmentioning
confidence: 96%
“…In parallel with ultrastructural studies mapping solute distributions in the capillary wall, seminal studies by Brenner and Deen using inert tracers suggested that glomerular transport of negatively charged solutes was much lower than that of comparably sized neutral solutes (5,23,33,34). Subsequent work by Comper and colleagues (7,38) attributed the measured difference in urine concentrations of neutral and sulfated dextrans to desulfation of the dextran during its passage across the capillary wall. Multiple investigators have published studies comparing charged and neutral proteins consistent with a glomerular charge barrier (4,30).…”
mentioning
confidence: 94%
“…However, this proved to be an erroneous conclusion because it was later demonstrated that the apparent charge selectivity could be destroyed by merely increasing the concentration of circulating dextran sulfate [13]. This was related to the fi nding that dextran sulfate was not an inert transport probe [14] but was desulfated by endothelial cells [15]. The process was saturable because at higher concentrations there was no desulfation and no apparent charge selectivity [13].…”
Section: Gsc Of Negatively Charged Transport Probesmentioning
confidence: 94%
“…Subsequently it was demonstrated that dextran sulfate is desulfated during filtration in vivo (27) and that this cell-mediated desulfation process is responsible for the apparent differences in glomerular sieving of dextran sulfate compared with uncharged dextran (16,124). Dextran sulfate itself does not bind to albumin (16) under physiological conditions, and therefore this does not contribute to apparent differences in transglomerular transport.…”
Section: Charge Selectivity Cannot Account For the Low Glomerular Permentioning
confidence: 98%